THE INFLUENCE OF OUTDOOR GAMES ON THE RESTORATION OF THE PSYCHOLOGICAL COMFORT OF STUDENTS IN THE UNIQUE EDUCATIONAL SPACE OF "T-UNIVERSITY" DSTU - Mavropoulo O.S.; Tumasyan T.I.; Brovashova O.Yu.; Brovashov N.S. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the impact of outdoor games on the psychological state of students in the conditions of "T-University". Methods and structure of the study. Within the framework of the unique educational space "T-University", built on the principles of individual educational trajectories, a program was implemented to teach students outdoor games in accordance with their priorities in sports. In the course of mastering the program, the psychophysical state of the trainees was corrected. Results and conclusions. Outdoor games contributed to the elimination of the psychological depression of those involved, increasing the degree of adaptation in the team, self-esteem, the formation of a focus on changing the situation for the better, improving physical condition and increasing efficiency, getting rid of aggression.